Karakteristik Klinis, Keluhan Utama, dan Gambaran Pencitraan MRI pada Pasien Makroadenoma Pituitari di RSUD Dr. Saiful Anwar: Karakteristik Klinis, Keluhan Utama, dan Gambaran Pencitraan MRI pada Pasien Makroadenoma Pituitari di RSUD Dr. Saiful Anwar - Saputra, Anggadha; Normahayu, Indrastuti; Bahasa Indonesia, Bahasa Indonesia (RSUD Dr. Saiful Anwar Province of East Java, 2025)
ntroduction: Pituitary macroadenomas are benign neoplasms of the pituitary gland that often cause significant mass effects, such as compression of the optic chiasm and cavernous sinus, as well as hormonal disturbances. Studies on the demographic characteristics, chief complaints, and imaging features of pituitary macroadenomas in Indonesia remain limited. This study aims to provide a comprehensive overview of patients with pituitary macroadenomas at Saiful Anwar General Hospital. Objective: This study aims to analyze the demographic distribution, clinical complaints, and MRI imaging characteristics of patients with pituitary macroadenomas. Methods: This retrospective descriptive study involved 23 patients who underwent brain MRI at Saiful Anwar General Hospital between January 2020 and December 2024. Demographic data, chief complaints, and MRI imaging findings were analyzed descriptively. Variables evaluated included age, gender, chief complaints, tumor consistency, and signal intensity on T1- and T2-weighted sequences. Results: Among the 23 patients, 82.6% were female, with a mean age of 46.95 years. The most frequently reported complaint was blurred vision (43.5%), caused by optic chiasm compression. Most tumors were solid (69.6%), with hyperintensity dominance on T2-weighted sequences (78.3%). Suprasellar extension was observed in most patients, involving the optic chiasm and cavernous sinus. Conclusion: Pituitary macroadenomas are more commonly found in middle-aged females, with visual disturbances being the dominant complaint. MRI revealed solid consistency with signal heterogeneity, emphasizing the importance of radiological evaluation for early diagnosis and therapeutic planning. A multidisciplinary approach is essential to improve patient quality of life.